Fetal Growth Trajectories Among Small for Gestational Age Babies and Child Neurodevelopment. Issue 5 (3rd June 2021) - Ferguson, Kelly K.; Sammallahti, Sara; Rosen, Emma; van den Dries, Michiel; Pronk, Anjoeka; Spaan, Suzanne; Guxens, Mònica; Tiemeier, Henning; Gaillard, Romy; Jaddoe, Vincent W.V.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Being born small for gestational age (SGA, <10th percentile) is a risk factor for worse neurodevelopmental outcomes. However, this group is a heterogeneous mix of healthy and growth-restricted babies, and not all will experience poor outcomes. We sought to determine whether fetal growth trajectories can distinguish who will have the worst neurodevelopmental outcomes in childhood among babies born SGA. Methods: The present analysis was conducted in Generation R, a population-based cohort in Rotterdam, the Netherlands (N = 5, 487). Using group-based trajectory modeling, we identified fetal growth trajectories for weight among babies born SGA. These were based on standard deviation scores of ultrasound measures from mid-pregnancy and late pregnancy in combination with birth weight. We compared child nonverbal intelligence quotient (IQ) and attention deficit hyperactivity disorder (ADHD) symptoms at age 6 between SGA babies within each growth trajectory to babies born non-SGA. Results: Among SGA individuals (n = 656), we identified three distinct fetal growth trajectories for weight. Children who were consistently small from mid-pregnancy (n = 64) had the lowest IQ (7 points lower compared to non-SGA babies, 95% confidence interval [CI] = −11.0, −3.5) and slightly more ADHD symptoms. Children from the trajectory that started larger but were smaller at birth showed no differences in outcomes compared to children born non-SGA. Conclusions: Among SGA children, those who were smaller beginning in mid-pregnancy exhibited the worst neurodevelopmental outcomes at age 6. Fetal growth trajectories may help identify SGA babies who go on to have poor neurodevelopmental outcomes.